2019
DOI: 10.1007/978-3-030-17462-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Building Better Bit-Blasting for Floating-Point Problems

Abstract: An effective approach to handling the theory of floatingpoint is to reduce it to the theory of bit-vectors. Implementing the required encodings is complex, error prone and requires a deep understanding of floating-point hardware. This paper presents SymFPU, a library of encodings that can be included in solvers. It also includes a verification argument for its correctness, and experimental results showing that its use in CVC4 out-performs all previous tools. As well as a significantly improved performance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…We note that it is in principle possible to encode the queries using the floating-point theory, and thus to encode the semantics of the loop body, including roundoff errors, exactly. However, despite the recent advances in floating-point decision procedures [8], we have observed that their performance is still prohibitively slow for our purpose (CVC4's state-of-the-art floating-point procedure [8] was several orders of magnitude slower than Z3's real-valued procedure [24]).…”
Section: Floating-point Invariantmentioning
confidence: 96%
“…We note that it is in principle possible to encode the queries using the floating-point theory, and thus to encode the semantics of the loop body, including roundoff errors, exactly. However, despite the recent advances in floating-point decision procedures [8], we have observed that their performance is still prohibitively slow for our purpose (CVC4's state-of-the-art floating-point procedure [8] was several orders of magnitude slower than Z3's real-valued procedure [24]).…”
Section: Floating-point Invariantmentioning
confidence: 96%
“…Similarly, bounded model checking [52] is limited by the performance of the underlying SAT/SMT solvers. While the floating-point support in today's SMT solvers [17,16] has improved significantly in recent years, it is still limited to relatively few arithmetic expressions.…”
Section: Related Workmentioning
confidence: 99%
“…While the extension was optimized for this task, we stress that our techniques are theory-agnostic and can be used for synthesis problems over any finite domain. Our approach builds upon the SyGuS capabilities of the SMT solver CVC4 [5,29], which has recently been extended to support reasoning about the theory of floating-points [11]. We use the invertibility condition for floatingpoint addition with equality here as a running example.…”
Section: Synthesis Of Floating-point Invertibility Conditionsmentioning
confidence: 99%
“…Problems that combine universal quantification over floating-points are rare-experience to date has suggested they are hard for solvers and would-be users should either give up or develop their own incomplete techniques. However, progress in theory solvers for floating-point [11] and the use of expression synthesis for handling universal quantifiers [27,29] suggest that these problems may not be entirely out of reach after all, which could potentially impact a number of interesting applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation